2021
DOI: 10.18240/ijo.2021.06.19
|View full text |Cite
|
Sign up to set email alerts
|

Commentary review: challenges of intraocular lens implantation for congenital cataract infants

Abstract: As an indispensable part of congenital cataract surgery, intraocular lens (IOL) implantation in infantile patients has long-term positive impacts on visual rehabilitation, as well as postoperative complications inevitably. Timing of IOL implantation in infantile congenital cataract patients is not simply a point-in-time but a personalized decision that comprehensively takes age at surgery, risks of postoperative complications, and economic condition of family in consideration, and combines with choosing suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Zhao et al reported that age at surgery and laterality of cataract were two important factors when judging the optimal timing of IOL implantation. It was also recommended to delay the IOL implantation to reduce postoperative complications in a bilateral cataract 18 . The present results are similar to the recommendations of these literatures; children who underwent primary IOL implantation were significantly older than the others, and secondary IOL implantation was performed later in the bilateral cataract cases compared to the unilateral cataract cases.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al reported that age at surgery and laterality of cataract were two important factors when judging the optimal timing of IOL implantation. It was also recommended to delay the IOL implantation to reduce postoperative complications in a bilateral cataract 18 . The present results are similar to the recommendations of these literatures; children who underwent primary IOL implantation were significantly older than the others, and secondary IOL implantation was performed later in the bilateral cataract cases compared to the unilateral cataract cases.…”
Section: Discussionmentioning
confidence: 99%
“…Cataract extraction followed by secondary intraocular lens (IOL) implantation is a common treatment strategy for infantile cataract patients (Lim et al., 2017; Zhao & Zhao, 2021). In most paediatric aphakic eyes, secondary IOL implantation into the ciliary sulcus is performed due to insufficient residual lens capsule after cataract extraction or failure to reopen the capsular bag due to firmly adherent capsular leaflets (Kleinmann et al., 2013; Liu et al., 2022; Shenoy et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…E ven with the development of modern microsurgical techniques and equipment, complications following pediatric cataract surgery still remain challenging [1][2][3][4] . The Infant Aphakia Treatment Study (IATS) found that common intraocular complications include visual axis opacification, glaucoma, and intraocular lens (IOL) exchange [5][6] .…”
Section: Introductionmentioning
confidence: 99%